2011
DOI: 10.4028/www.scientific.net/amr.214.412
|View full text |Cite
|
Sign up to set email alerts
|

YSZ-Reinforced Ni-P Deposit: An Effective Condition for High Particle Incorporation and Porosity Level

Abstract: Nickel ceramic composite have emerged as potential corrosion, wear and thermal resistance. The present work contemplates reinforcement of Ni-P deposits with YSZ ceramic by electroless nickel deposition technique. The ratio of metal nickel (Ni) to ceramic yttria stabilized zirconia (YSZ) in composite materials determines its ability in corrosion, thermal, wear resistance. The amount of porosity enhances thermal insulation. The 2k full factorials design of experiment and analysis of variance (ANOVA) were used in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…There are two sizes of 8YSZ used, micro-sized with of nominal diameter of 2 m and nano-sized particles ranging between 100-500 nm. The optimum particle loading is in the range of 5-10 g/L as used by Baba et al, [9]. The particle loading for both sizes used is 10 g/L and the mixed particle size is by a ratio of 1:1.…”
Section: Methodology 21 Materials Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two sizes of 8YSZ used, micro-sized with of nominal diameter of 2 m and nano-sized particles ranging between 100-500 nm. The optimum particle loading is in the range of 5-10 g/L as used by Baba et al, [9]. The particle loading for both sizes used is 10 g/L and the mixed particle size is by a ratio of 1:1.…”
Section: Methodology 21 Materials Preparationmentioning
confidence: 99%
“…The incorporation of ceramic particles into the Ni-P deposit produces a cermet such as silicon carbide work done by Ahmadkaniha et al, [4], nano-diamond and diamond work done by Mirhosseini et al, [6] and Trzaska et al, [7], and cubic boron nitride by Norsilawati et al, [8]. The influence of electroless coating parameters play an important effect on the deposit quality and the incorporation of particle quantity can be enhanced by using smaller size particle, stirring agitation, and blasting surface treatment as reported by Baba et al, [9]. It was also found by Ashtiani et al, [10] that different types of complexing agents in the electroless nickel bath also give affect the deposit properties.…”
Section: Introductionmentioning
confidence: 95%
“…As seen in Table 2, the deposit structure changes because the phosphorus or boron content changes. EN bath concentration, temperature, pH, agitation, and bath loading effect the EN process [14].…”
Section: Electroless Nickelmentioning
confidence: 99%
“…[6] [7] (iv) Electroless Plating The final step in the process is the nickel coating. There are two sub-steps relating to the chemistry within the coating, the initial phase and the auto-catalytic phase.…”
Section: (Ii) Pre-catalystmentioning
confidence: 99%
“…Around 20-40% is accepted as an adequate level of porosity (6). Baba et al (7) investigated the effect of particle size, agitation method, substrate condition and bath pH on porosity. They found that the level of porosity was increased by using a combination of small particle size (2 µm instead of 10 µm).mechanical stirring agitation and a substrate surface treatment of mechanical blasting.…”
Section: Porositymentioning
confidence: 99%